Democracia e socialismo no pensamento de Leandro Konder (1935-2014) - Oliveira, Mateus Tuzzin de (2018)
The present work sought to investigate the political thinking of Leandro Konder (Rio de Janeiro, December 31, 1935 - Rio de Janeiro, November 12, 2014) from the perspective of the relationship between democracy and socialism found in his works. Philosopher, novelist, poet, translator and intellectual, the author consisted of one of the most important names of Brazilian Marxism of the second half of the twentieth century. In order to study the relationship between democracy and socialism in Konder's thought, the research resorted to the methodological subsidies provided by Quentin Skinner's linguistic contextualism and the sociology of the intellectuals. The main texts used in the approach to the author's thinking were the books Democracy and Communists in Brazil (1980) and The Future of Philosophy of Praxis: Marx's Thinking in the 21st Century (1992). The research was justified based on the influence of Konder's production, on the scarcity of works on his work and on its relevance as an exponent of a lineage of Brazilian political thought, that of Marxism of communist matrix. In the study of the political evolution of the author on the binomial democracy-socialism, the research was conducted based on two hypotheses. 1) The main hypothesis was the conception that in the socialism-democracy relationship, Konder's thinking was oriented, in the leftist political sphere, to the strengthening of the idea of democracy, and theoretically, for the renewal of Marxism in the country. 2) On the other hand, as a secondary hypothesis and linked to the previous, was suggested that the developments in Konder's thinking were made in the sense of a departure from Leninism in favour of another modality of Marxism, in theory, and a distancing of the Soviet experience in favour of another model of socialism, in the politico-practical scope. The exposition of the results of the investigation pointed the full confirmation of the main hypothesis and the partial validity of the secondary hypothesis. The conclusions were made possible by the presentation, in the second chapter of the paper, of the way in which the question of democracy and socialism appeared (1) in Jean-Jacques Rousseau's radical and petty bourgeois conception of democracy; 2) in the understanding of the classical authors of the Marxist tradition (Karl Marx, Friedrich Engels and Vladimir Ilyich Ulyanov Lenin); 3) in the view of the exponents of economic liberalism (Joseph A. Schumpeter) and political liberalism (Norberto Bobbio). It was found that Konder approached the idea of democracy present in Rousseau and Norberto Bobbio, while moving away from the understanding present in the Marxist authors. In the Brazilian context, this movement was expressed at the adherence to the political line of the Declaration of March 1958, a document of the Brazilian Communist Party (PCB), at the affiliation with the presuppositions of Eurocommunism and at the political evaluation extracted from an interpretation of the Brazilian reality inspired in Antonio Gramsci’s (1891-1937) ideas.